The Manufacturing Revolution and the Quest for an Individuality (International Journal of Innovative Research in Engineering & Management, 2021)
The Fourth Industrial Revolution (industry 4.0) promises a  connected and smart production system in which the Internet,  the machines (physical systems) and humans are all joined  together. Unlike previous economic booms, current  industrialisation primarily relies on Information Technology  (IT). Private information is generated and shared often via  interactions between the device and the device and the machine.  Personal information is already a new commodity, and is now  known as a "newoil" or a "new arena of battle." The more  information is generated and collected, the more complete and  risky the personal data is. Although privacy and security are  frequently combined, they are different concepts. This study  aims to investigate different vectors of the privacy hazard of  Industry 4.0. This study examines data breach incidents, the  problems of privacy, legal obligations as well as the need for  knowledge of contextual privacy. This research ends with the  explanation of the dangers connected with the divulgation of  PIIs in the era of Industry 4.0. Scientific advancement will in  future lead to an inventory miracle with long-term efficiencies  and productivity benefits. Transport and communications will  decrease, logistics and global distributors will improve and price  levels will fall, new markets will be created and economic  development promoted.
Keywords: Communication; Fourth Industrial Revolution; Industry 4.0; Privacy; Security